Effects of graded versus ungraded individual readiness assurance scores in team-based learning : a quasi-experimental study - Koh, Juliana Ying Yun (2021)
Pre-class preparation is a crucial component of team-based learning (TBL). Lack of preparation hinders both individual learning and team performance during TBL. The purpose of the present study was to explore how the grading of the individual readiness assurance test (iRAT) can affect pre-class preparation, iRAT performance and performance in the end-of-year examination. Using a quasi-experimental design, Year 1 and 2 students' download frequency for their pre-class materials, performance on iRAT and examination were examined under two conditions; (1) under which the iRAT was graded and (2) under which the iRAT was ungraded. Medical students (N = 220) from three cohorts were included in the study. Differences between both conditions were tested by means of six separate ANCOVAs, using medical school entry test scores as the covariate to account for potential cohort effects. Results revealed that students were downloading more pre-class materials prior to their TBL sessions, and were performed significantly better on iRAT when their performance was graded, even after controlling for cohort effects. Analysis of covariance demonstrated that performance on iRAT also appeared to affect performance on their examination scores. The results of the study suggest that grading has a positive effect on students' iRAT scores. Implications for TBL are discussed.